Selective area fabrication of carbon nanostructures using alcohol catalytic chemical vapor deposition and spin on glass - Fauthan, Aishah (2015)
The thesis describes an investigation on selective area fabrication of carbon nanostructures as a technique for sensor application. Nowadays, the researchers are using spraying technique for selective area of carbon nanostructure. However due to adhesion issues, different fabrication processes are investigated to overcome the problem. The alcohol catalyst chemical vapor deposition (ACCVD) has been chosen as the technique to synthesis the carbon nanostructure. Different parameters of carbon nanostructures process synthesis using ACCVD are tested. Catalyst preparation method and temperature are varied to produce the best parameter for carbon nanostructures growth. It was evident that using impregnation method of catalyst and mixed of ethanol gives a good result in carbon nanostructures growth. The temperature effect is investigated by varying the temperature value using 750°C, 800°C and 850°C. The growth of carbon nanostructures showed that the quality of yield increased with increasing temperature. For the selective area fabrication, two materials had been investigated as the layer for the carbon nanostructure growth which are resist and spin on glass. The ability of materials to withstand the high temperature phase is considered in the beginning of selection for the selective layer fabrication. The etching method and lithography process is proposed as a method to solve the problems in selective area fabrication of carbon nanostructure. The SOG is more suitable compared to resist AZ1500 in ACCVD nanostructures synthesis method due to high temperature requirement. The pretreatment processes method in hydrogen gas at 425°C for SOG is necessary for high quality layer. This method is known as annealing process to make the SOG harder, tougher and more stable in high temperature condition in synthesis process. The thickness and etching rate time of SOG is also investigated for the selective area fabrication. The samples of 0.42μm SOG is immersed in buffered oxide etch solution for five minutes to create a selective layer.